Retroperitoneal leiomyosarcoma invading the renal hilum: A case report and literature review - Hongyan Song, MB; Fang Nie, MD (Radiology Case Reports)
A 62-year-old male patient was admitted to our hospital due to abdominal pain. Imaging studies, including computed tomography (CT) and ultrasonography, revealed a space-occupying lesion in the left renal hilar region. Postoperative pathological examination confirmed the diagnosis of retroperitoneal leiomyosarcoma with renal involvement. This report details the clinical manifestations, imaging characteristics, histopathological findings, and therapeutic management of this case. Additionally, a literature review on retroperitoneal leiomyosarcoma is provided. The aim of this article is to enhance the diagnostic experience of clinicians, radiologists, and sonographers, thereby improving the preoperative diagnostic accuracy for retroperitoneal leiomyosarcoma.